Gangrene or Cancer? Sixteenth-Century Medical Texts and the Decay of the Body of the Church in Jean Calvin’s Exegesis of 2 Timothy 2:17 - Starkey, Lindsay J. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2016)
In 2 Timothy 2:17, Paul compared the effects of false teachings on the Church to a disease. Rejecting previous translations that identified this disease as cancer, Jean Calvin (1509–64) insisted that it must be gangrene in his 1548 commentary on this epistle, citing and discussing medical texts to justify his translation. This article places his commentary in the context of these medical texts. The causes, courses, and treatments his contemporaries associated with gangrene provide insight into Calvin’s idea of the people likely to spread false teachings and of how they should be treated: because, for him, the experience of gangrene reflected the real effects of false teachings on the Church. This manuscript argues that consulting other areas of sixteenth-century knowledge, such as medicine, was a part of Calvin’s exegetical practice. It also suggests that modern scholars need to take these other areas of knowledge into account when analyzing sixteenth-century biblical commentaries.